PRINCIPLES OF RECEPTION REMOTE «QUASIANGLE» RADAR-TRACKING PORTRAITS IN THE PEAK MONOPULSE DIRECTION FINDER - S. A. Gorshkov; E. N. Builov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The principles of range - quasiangle radiolocation portrait receiving in peak monopulse bearer where summary - differential handling is carried out not at superhigh frequency but at videofrequency with digital signal processing are discussed. The results of radiolocation portrait mathematical modeling are shown.